1980
DOI: 10.1186/1297-9686-12-2-143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the m gene for muscular hypertrophy on conformation at one year of age in beef cattle

Abstract: SummaryNinety-five calves, mostly Angus, but also of Hevefovd and Shovthovn breeding, born in the University of California herd, were studied, including 54 , born during Spring 1970 , genotypically distributed as 7 mm, 33 m-!-and 14 + + (m being the symbol for the autosomal allele for doublemuscling).Conformation was evaluated at yearling age by scoring superficial muscles for bulginess and the lateral shape of the rump, and combining the scores into an index (h). Differences between mm and m + and between m-!… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This may be detrimental for the blood circulation in the hooves and the formation of new horn. This is confirmed by the undersized limb bones in DM-animals [ 44 ] and the smaller circumference of the canon bone [ 108 ] and the femur [ 48 ]. Inhibition of collagen synthesis in connective tissues may also attenuate mechanical and structural adaptation of tendons and ligaments.…”
Section: Consequences Of the Inactivation Of Myostatin On Conformamentioning
confidence: 85%
“…This may be detrimental for the blood circulation in the hooves and the formation of new horn. This is confirmed by the undersized limb bones in DM-animals [ 44 ] and the smaller circumference of the canon bone [ 108 ] and the femur [ 48 ]. Inhibition of collagen synthesis in connective tissues may also attenuate mechanical and structural adaptation of tendons and ligaments.…”
Section: Consequences Of the Inactivation Of Myostatin On Conformamentioning
confidence: 85%
“…[12,13,17,19,21]; also reviewed by Arthur [3]); and (ii) results of studies where crossbred animals were directly genotyped [4,5]. While such studies act as benchmarks for the current study, the results of both sets need to be confirmed for a single population with a segregating del11 allele.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the key information required is the way in which the del11 allele affects traits of economic importance. There is information available in the literature on the effects of double muscling on weight [4,5,19], muscling [4,21] and calving difficulty [5]. However, this information is limited in two ways.…”
Section: Introductionmentioning
confidence: 99%
“…Double muscling is an inherited character which is determined by one major gene (rr) whose expression is influenced by polygenic (modifying genes) and non-genetic (environmental) effects (Nott and Rollins 1979). However, Menissier (1982) suggested the possibility of a polygenic determination of double mus-cling as an all-or-nothing trait.…”
mentioning
confidence: 99%